Evidence of Reciprocal Allonursing in Reindeer, Rangifer tarandus. (21st November 2014) - Engelhardt, Sacha C.; Weladji, Robert B.; Holand, Øystein; Røed, Knut H.; Nieminen, Mauri; Ebensperger, L.
Abstract The nursing of non‐offspring is referred to as allonursing. Reciprocity is a hypothesized cause of allonursing, but previous studies have not strongly supported or found no evidence in support for this hypothesis. Biological market theory was applied to 25 reindeer (Rangifer tarandus) does and their calves to investigate allonursing reciprocity across bouts and within dyads and assess the diversity of allonursing partners. We also investigated whether variation in allonursing would be associated to relatedness within dyads. We recorded both the occurrence and the duration of 1027 successful allonursing solicitations. All does allonursed, and only three of the 25 calves were not observed being allonursed. Throughout the study, 234 allonursing dyadic pairs were observed. Does allonursed the calves of several does, but allonursing was not distributed evenly among all potential partners. Twenty does were members of at least 1 dyad with a high degree of reciprocity based on the number of allonursing bouts exchanged within the dyad. We found evidence of both relative and absolute allonursing reciprocity at the group level. Across bouts and within dyads, the reciprocal allonursing indexes varied greatly both for frequency and for duration, with an average tendency towards unidirectionality. Evidence of strong reciprocity within dyads was found in 32 dyads for number of allonursing bouts and in 25 dyads for duration of allonursing bouts. Across bouts and within dyads, the number of allonursing bouts received was not influenced by relatedness, allonursing bouts given or absolute rank difference. Allonursing was not interchanged for rank‐related benefits. Our results provide evidence of reciprocal allonursing at the group level, across bouts and within dyads, and reciprocal allonursing among chosen partners. Our results point to the usefulness of applying the biological market theory to allonursing and of considering allonursing as a tradable commodity, traded for itself, among chosen partners.